2014
DOI: 10.1097/sap.0b013e318284eca0
|View full text |Cite
|
Sign up to set email alerts
|

Study on Distribution of Terminal Branches of the Facial Nerve in Mimetic Muscles (Orbicularis Oculi Muscle and Orbicularis Oris Muscle)

Abstract: There have been many anatomical reports to date regarding the course of the facial nerve to the mimetic muscles. However, reports are relatively scarce on the detailed distribution of the terminal branches of the facial nerve to the mimetic muscles. In this study, we performed detailed examination of the terminal facial nerve branches to the mimetic muscles, particularly the branches terminating in the orbicularis oculi muscle and orbicularis oris muscle. Examination was performed on 25 Japanese adult autopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“… 8 While according to the references, most of the surgeons think that the upper orbicularis oculi muscle innervated by temporal branch of facial nerve, 10 there is conflicting evidence about the innervation of orbicularis oculi muscle fibers in the upper eyelid region as well as the course of buccal branch of the facial nerve. 11 , 12 According to these precise anatomical studies the terminal fibers of buccal branch of facial nerve, coursing from lateral parts of the bony pyramid of nose are responsible for innervating the medial part of upper eyelid orbicularis muscle. The course of these fibers is compatible with lateral nasal osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
“… 8 While according to the references, most of the surgeons think that the upper orbicularis oculi muscle innervated by temporal branch of facial nerve, 10 there is conflicting evidence about the innervation of orbicularis oculi muscle fibers in the upper eyelid region as well as the course of buccal branch of the facial nerve. 11 , 12 According to these precise anatomical studies the terminal fibers of buccal branch of facial nerve, coursing from lateral parts of the bony pyramid of nose are responsible for innervating the medial part of upper eyelid orbicularis muscle. The course of these fibers is compatible with lateral nasal osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
“…Orbicularis oculi function is spared following frontal branch injury as the muscle receives dual innervation in the form of a second nerve supply from the zygomatic branch, but this seems to be limited to the inferior region. Mitsukawa et al () examined the branches of the terminal facial nerve and the mimetic muscles in detail in 25 Japanese adult autopsies. They reported that the temporal branch (they did not separate the frontal and temporal branches) was connected to the orbicularis oculi muscle in all cases and that the marginal mandibular branch was always connected with the orbicularis oris muscle.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large diversity regarding the number of BB which has been reported to be composed of 1 to 5 branches. [1,3,4,16,[19][20][21] Only a single BB has been reported to be found 2.5% to 85%, two branches 15% to 50%, three branches 48.6% and four branches 5.7%. [11,[22][23][24] In the present study, the mean number of BB was identified as 2.40±0.62 (range: 1-4) branches proximally and 4.03±1.03 (range: 2-6) branches distally.…”
Section: Discussionmentioning
confidence: 99%
“…Deep twigs of the BB innervate the zygomaticus major and minor, levator labii superioris, levator anguli oris, levator labii superioris alaeque nasi, small nasal muscles, buccinator and orbicularis oris muscles. [1][2][3][4] Zygomatic branches of the facial nerve (ZB) cross the zygomatic bone towards lateral canthus and innervate orbicularis oculi muscle. These branches may also con-tribute innervation of the muscles which are innervated by the BB.…”
Section: Introductionmentioning
confidence: 99%